Perpetrators of domestic violence abuse within Intellectual Disability services: A hidden population?. (6th February 2018) - Swift, Charlotte; Waites, Erin; Goodman, Wendy
Abstract : Accessible Summary: Domestic violence abuse is when people hurt family members or partners with their words or actions, take their money or try to control them. It is against the law to do this. We wanted to know more about how many people with intellectual disabilities are being violent in their relationships. Forensic Community Learning Disabilities Team (CLDT) noticed more people were being referred to the team because they had been violent in their relationships. The Forensic CLDT looked at their referrals to see how many people were violent in their relationships. They also looked at referrals for their local Community Learning Disabilities Teams to see how many people were violent in their relationships. The research showed that more people who were referred to the Forensic CLDT needed help for violence in their relationships in 2015. The CLDTs also had referrals for people who were violent in their relationships. It is important to understand more about people with intellectual disabilities who are abusive in their relationships so we can help them. Abstract: Background: Domestic violence abuse (DVA) has been identified by the UK Government as a priority to address. Whilst there is a growing body of research into perpetrators of DVA from the mainstream population, there is scant research into perpetrators of DVA who have an intellectual disability. This lack of an evidence base suggests there may be a group of individuals for whom there is no suitable treatment approach. A Forensic Community Learning Disabilities Team (FCLDT) completed a multiservice evaluation of their service and sector CLDTs to obtain a measure of local unmet need. Materials and methods: A retrospective review was completed for referrals to the FCLDT and four of their sector CLDTs for 2014 and 2015. A record sheet was designed for the process of data collection and the analysis of referrals. Results: In regard to the FCLDT, 14% of the total referrals made to the FCLDT in 2014 referenced DVA perpetration and the figure rose to 26% in 2015. For CLDTs, 1.9% of the total referrals made to the CLDT in 2014 and 3.18% in 2015 referenced DVA perpetration. Conclusions: A significant proportion of referrals to the Forensic CLDT relate to the perpetration of domestic violence abuse. A proportion of Sector CLDT referrals made reference to behaviours that, according to the Home Office definition, would be classified as domestic violence abuse, but was infrequently referred to as such. The paper considers these findings in the light of the Home Office definition and its application to people with intellectual disabilities.